International Commodity Price Shocks, Democracy, and External Debt - Bruckner, Markus (IMF Working Papers; Working Paper, 2010)
We examine the effects that international commodity price shocks have on external debt using panel data for a world sample of 93 countries spanning the period 1970-2007. Our main finding is that positive commodity price shocks lead to a significant reduction in the level of external debt in democracies, but to no significant reduction in the level of external debt in autocracies. To explain this result, we show that positive commodity price shocks lead to a statistically significant and quantitatively large increase in total government expenditures in autocracies. In democracies on the other hand government expenditures did not increase significantly. We also document that following positive windfalls from international commodity price shocks the risk of default on external debt decreased in democracies, but increased significantly in autocracies.